1.
а)
x = 1-2y
(1-2y)y=-1
-2y^2+y+1=0
D=9
y1=-1+3/-4=-0.5
y2=-1-3/4=1
x1=2
x2=-1
б)
x=4+y
(4+y)^2 + (4+y)y = 6
16+8y+y^2+4y+y^2-6=0
2y^2+12y+10=0 /2
y^2+6y+5 = 0
D=16
y1 = -6+4/2 = -1
y2 = -6-4/2 = -5
x1 = 4-1=3
2.
4x^2-xy=6
7x^2=28
x^2=4
x1 = 2
x2 = -2
4*2^2-2y=6
y = 5
4*(-2)^2+2y=6
2y = -10
y = -5
1.а) x+2y=1 xy=-1x=1-2yy(1-2y)=-1y-2y^2+1=02y^2-y-1=0D=1+4*2=9=3^2Y1=1+3/4=1Y2=1-3/4=-2/4=-0,5X1=1-2=-1X2=1-2(-0?5)=0ответ: X1=-1 X2=0 Y1=1 Y2=-0,5б) x^2+xy=6 x-y=4
x=4+y(4+y)^2+(4+y)*y=616+8y+y^2+4y+y^2=6
2y^2=12y+10=0y^2+6y+5=0D=36-4*5=16=4^2Y1=-6+4/2=-1Y2=-6-4/2=-5X1=4+(-1)=3X2=4+(-5)=-1ответ: X1=3 X2=-1
Y1-1 Y2=-52. 4x^2-xy=26 3x^2+xy=2 7x^2=28 x^2=4 X1,2=+-2Y1=26-16/2=5Y2= 26-16/-2=-5ОТвет: X1=3 X2=-1 Y1=5 Y2=-5
1.
а)
x = 1-2y
(1-2y)y=-1
-2y^2+y+1=0
D=9
y1=-1+3/-4=-0.5
y2=-1-3/4=1
x1=2
x2=-1
б)
x=4+y
(4+y)^2 + (4+y)y = 6
16+8y+y^2+4y+y^2-6=0
2y^2+12y+10=0 /2
y^2+6y+5 = 0
D=16
y1 = -6+4/2 = -1
y2 = -6-4/2 = -5
x1 = 4-1=3
x2=-1
2.
4x^2-xy=6
7x^2=28
x^2=4
x1 = 2
x2 = -2
4*2^2-2y=6
y = 5
4*(-2)^2+2y=6
2y = -10
y = -5
1.
а) x+2y=1
xy=-1
x=1-2y
y(1-2y)=-1
y-2y^2+1=0
2y^2-y-1=0
D=1+4*2=9=3^2
Y1=1+3/4=1
Y2=1-3/4=-2/4=-0,5
X1=1-2=-1
X2=1-2(-0?5)=0
ответ: X1=-1 X2=0
Y1=1 Y2=-0,5
б) x^2+xy=6
x-y=4
x=4+y
(4+y)^2+(4+y)*y=6
16+8y+y^2+4y+y^2=6
2y^2=12y+10=0
y^2+6y+5=0
D=36-4*5=16=4^2
Y1=-6+4/2=-1
Y2=-6-4/2=-5
X1=4+(-1)=3
X2=4+(-5)=-1
ответ: X1=3 X2=-1
Y1-1 Y2=-5
2. 4x^2-xy=26
3x^2+xy=2
7x^2=28
x^2=4
X1,2=+-2
Y1=26-16/2=5
Y2= 26-16/-2=-5
ОТвет: X1=3 X2=-1
Y1=5 Y2=-5